(untitled) (Research, Society and Development, 2020)
The objective of this study was to determine whether inoculating honey from Apis mellifera into broiler chick eggs (in ovo nutrition) during incubation would improve hatchability and performance. Initially, four hundred eggs were incubated; at 12 days of incubation, ovoscopy was performed to select the fertile eggs and divide them into three groups: control, saline and honey groups. On the 17th day of incubation we inoculated 0.2 mL of each solution directly into the amniotic cavity. After hatching, the chicks were housed in an experimental house until 28 days of age, when two birds per experimental unit were sacrificed to evaluate carcass yield. The hatchability was not affected by inoculation of saline or honey (p>0.05). However, mortality was higher in the honey and saline groups than in the control group (p<0.05). The birds that received in ovo nutrition with bee honey had a body weight 11% higher than 28 days compared to the control. The honey group showed better feed conversion and greater heart weight at 28 days (p<0.05). Mortality, carcass yield and bowel variables did not differ between treatments (p>0.05). These results show that the in ovo nutrition with bee honey resulted in lower production costs, that is, the birds consumed less food (feed) and had the same weight gain as other treatments.